P65 Respiratory ill health in the silica exposed stone working sector. (12th November 2015) - Fishwick, D; Sumner, J; Barber, CM; Robinson, E; Codling, A; Lewis, L; Young, C; Warren, N
Abstract : Introduction: Exposure at work to inhaled respirable crystalline silica (RCS) has previously been linked with silicosis, tuberculosis, lung cancer and COPD. Whilst the risk of developing silicosis is largely a function of cumulative lifetime RCS exposures, current workplace exposures contribute to this risk. New cases of silicosis continue to be reported in the UK. The stone working sector is one where exposures to RCS continue to place workers at risk. Methods: A cross sectional GB based workplace study of stone workers was carried out, in order to identify a subsequent longitudinal cohort. Consenting workers were asked to complete an interviewer led questionnaire, undergo lung function testing and complete a full occupational history including details of lifetime exposure to RCS. Consenting workers had a PA Chest Radiograph using a mobile facility, and levels of RCS exposure in the personal breathing zone were measured. Results: 128 workers took part; with a mean age of 40.1 years and 11 years median (range 0.5–44) years worked overall in industry. One had radiological evidence of silicosis. Respiratory symptoms were common; for example 22.7% reported cough, 33.6% wheeze in the last 12 months, 16.4% reported ever having asthma. 14.1% reported at least one work related respiratory symptom. Mean lung function values (n = 127) were as follows; mean (SD) percentage predicted FEV1 97.5 (14.5) and FVC 103.6 (12.2). Twenty four workers had measured airways obstruction (as defined by an FEV1 /FVC <0.7); in this cross sectional analysis its presence did not significantly relate to current smoking status or duration of RCS exposure, although was associated with the reporting of a diagnosis of (ever having) asthma or chest tightness and difficulty in breathing. Conclusions: This cross sectional study of stone workers has identified a cohort for longer term follow up. Future work will allow the development dose response relationships (using measured current, and historic, RCS levels) corrected for other relevant factors, between cumulative RCS exposure and FEV1 decline. These approaches will assist in the development of future workplace interventions to reduce the health risks associated with RCS exposure in stone workers.